MIND MAPPING BERBANTUAN APLIKASI CANVA TERINTEGRASI PENDEKATAN TRI-N UNTUK MENGOPTIMALKAN KEMAMPUAN BERBICARA DI SEKOLAH DASAR - Reni Ulviyani; Siti Rochmiyati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Speaking is one of the most important skills for students to master in the 21st century. However, the reality on the ground shows that if almost all students are asked to speak during learning activities, it is still very worrying. The aim of this research is to describe the use of mind mapping assisted by the Canva application by integrating the Tri-N approach to optimize students' speaking abilities in class VI students at SDN 1 Sidomoro. The benefit of this research is to review the effectiveness of using mind mapping with the help of the Canva application which integrates Tri-N teachings on speaking skills in class VI students at SDN 1 Sidomoro. This research is included in the qualitative descriptive type. The data analysis technique used is guided by Miles and Huberman which consists of: 1) data collection, 2) data reduction, 3) data display, and 4) drawing conclusions/verification. In the initial assessment before the research was carried out, only 33.3% (4 students) were skilled at speaking. After the research was carried out, there was an increase of 83.3% (10 students) in proficiency and skill in speaking. So it can be concluded that by applying the mind mapping method assisted by the Canva application which is integrated with the Tri-N approach, it has proven to be effective in optimizing students' speaking abilities in class VI students at SDN 1 Sidomoro.